Pendidikan Agama Islam di MTsN 3 Batanghari Jambi - Asmadi, Asmadi; Subha, Habibah Aurora; Nurhidayat, Bella Rahma; Afrini, Novia; Nuralim, Ihsan; Naziva, Aviq (Medan Resource Center, 2024)
This study explores the implementation of Islamic Religious Education (PAI) at MTsN 3 Batanghari Jambi, emphasizing its role in fostering students’ spiritual, intellectual, and social growth. Employing a qualitative case study approach, data were gathered through in-depth interviews, participatory observations, and document analysis. The findings reveal an integrative educational model that combines interactive lectures, group discussions, case studies, and religious practice projects, enabling students to engage actively in contextual and reflective Islamic learning. Key challenges, including socio-economic diversity, globalization, and technological disruptions, are addressed through adaptive teaching strategies, digital integration, and continuous teacher professional development. The study demonstrates how PAI can go beyond traditional knowledge transfer, balancing theoretical understanding with practical spirituality. It provides valuable insights into contemporary Islamic education, offering recommendations such as flexible curricula, technology integration, innovative extracurricular activities, and teacher capacity building to create a transformative and inclusive educational environment.